Inter-regional variations and future household demand and production of major spices in India - M Hema, R Hasan, S K Srivastava, R Kumar, (Journal of Spices and Aromatic Crops, 2013)
India is the largest producer, consumer and exporter of spices in the world with around 52 spices under the purview of Spices Board. The present paper diagnoses the consumption and production pattern of the major spices in India both spatially and temporally and projects their demand and production in future using statistical tools. Spices basket was found to be dominated by drychilli and there exists wide regional variations in their consumption across the country. Production of spices follows the same pattern with dry-chilli occupying maximum area under cultivation. Projected figures confirmed domination of dry-chilli in future also. Region specific consumption as well as production of spices necessitates region specific production policies along with the suitable marketing strategies to increase the welfare of both producers as well as consumers.